Many levels of One: context and structure in Zhu Xi's concept of Li - Chew, S (2024)
Zhu Xi’s discussion on the oneness of Li involves two interrelated dimensions: 1) oneness of Li-content and 2) oneness of Li-form. The former dimension involves the unity of Li across various topical discussions like epistemology, metaphysics, ethics, and so on. For example, how metaphysical Li has moral implications, how Li can be both prescriptive and descriptive, and so on. The latter dimension accounts for the unity of Li across different structural relations: how different configurations of one and many Li relation are essentially one. These two dimensions are intricately interweaved as the structural relation or form is manifest in and expressed through the content of Li. Hence, the oneness of Li requires a holistic understanding involving both dimensions. However, the majority of contemporary scholarship focuses on the oneness of Li-content.